Representasi Karakter Autis Dalam Film Dancing in The Rain - Sarah Novita Diah; Sri Wijayanti (Jurnal Media dan Komunikasi Indonesia, 2020)
This research Focuses on how Indonesian movie portrays an autistic character. The Importance point of this research is because there is some misunderstanding around the society about people with autism. Dancing in The Rain is the most recent movie in Indonesia that held on 2018 and portrays about people with autism. That’s why this movie as an object for this research. This research used semiotic analysis by Roland Barthes, to giving enlightenment to the society about people with autism. This research finds that autistic character still used as a commodity to get sympathy from the audience. The interesting result that has been found for this movie, that this movie describe how people with autism can improve their social development as long as they grow up and get an autistic therapy.